Evaluating the Development Level of Agriculture in Kermanshah Province's Townships - Jafar Tavakkoli (جغرافیا و پایداری محیط)
This research assesses the agricultural development level of Kermanshah province's townships in order to provide appropriate context for regional development planning. To do this we employed 52 indicators, and after removing the differencs among indicators from various scales and weighing them using factor analysis method the final compositional indicator was determined. The results show that the most variation coefficient exists for agricultural infrastructures, work force and institutional composite indexes; Also Kermanshah and Eslamabad- e Gharb placed first and second in developmental ranking and Pave and Salas & Babajani ranked eleventh and twelfth. Furthermore Pearson correlation approved positive so that a significant relation was seen between infrastructure and institutional indexes with other agricultural sub-sectors development. Therefore focusing on balanced agriculture development in the province with more emphasis on infrastructure, institutional and work force development was recommended.